Activity-Dependent Regulation of Alternative Cleavage and Polyadenylation During Hippocampal Long-Term Potentiation - Mariana M. Fontes (Nature Portfolio, 2017)
Abstract Long-lasting forms of synaptic plasticity that underlie learning and memory require new transcription and translation for their persistence. The remarkable polarity and compartmentalization of neurons raises questions about the spatial and temporal regulation of gene expression within neurons. Alternative cleavage and polyadenylation (APA) generates mRNA isoforms with different 3′ untranslated regions (3′UTRs) and/or coding sequences. Changes in the 3′UTR composition of mRNAs can alter gene expression by regulating transcript localization, stability and/or translation, while changes in the coding sequences lead to mRNAs encoding distinct proteins. Using specialized 3′ end deep sequencing methods, we undertook a comprehensive analysis of APA following induction of long-term potentiation (LTP) of mouse hippocampal CA3-CA1 synapses. We identified extensive LTP-induced APA changes, including a general trend of 3′UTR shortening and activation of intronic APA isoforms. Comparison with transcriptome profiling indicated that most APA regulatory events were uncoupled from changes in transcript abundance. We further show that specific APA regulatory events can impact expression of two molecules with known functions during LTP, including 3′UTR APA of Notch1 and intronic APA of Creb1. Together, our results reveal that activity-dependent APA provides an important layer of gene regulation during learning and memory.